Government Policy and Social Inequality: A Critical Look at Regulations That Are Harmful to Society - Susianto; Sunarjo; Nurita, Riski Febria (Universitas Kristen Cipta Wacana, 2025)
This study aims to analyze the impact of government policies on social inequality in Indonesia, particularly through a critical review of regulations that have the potential to harm society. The primary focus of the study is a normative evaluation of the recent Job Creation Law (Law No. 6 of 2023) and other related policies that have sparked public debate regarding social justice and the protection of the rights of vulnerable groups. The method used is normative legal research with a document study approach and critical analysis of regulatory content based on the principles of constitutional law and social justice. The results show that although the 2023 Job Creation Law contains several improvements, government policies still tend to prioritize economic and investment interests, thus perpetuating social inequality due to unfair access to resources and legal protection. Furthermore, minimal public participation in the legislative process strengthens the position of elites and undermines substantive democracy. This study recommends the need for a paradigm shift in public policy towards a more inclusive and socially just approach to guarantee the rights of all Indonesians in accordance with the constitutional mandate